The great trouble : a mystery of London, the blue death, and a boy called Eel - Hopkinson, Deborah (New York : Yearling, an imprint of Random House Children's Books, 2015)
Eel, an orphan, and his best friend Florrie must help Dr. John Snow prove that cholera is spread through water, and not poisonous air, when an epidemic sweeps across their London neighborhood in 1854.
Includes bibliographical references (pages 245-247).
Middle School.
Accelerated Reader
Reading Counts!
660
Keywords: Snow, John, -- 1813-1858 -- Juvenile fiction; Cholera -- Juvenile fiction; Epidemics -- Juvenile fiction; Orphans -- Juvenile fiction; London (England) -- History -- 19th century -- Juvenile fiction; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Cholera -- Fiction; Epidemics -- Fiction; Orphans -- Fiction; London (England) -- History -- 19th century -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; Historical fiction; Medical fiction